Trump's bait and switch: Job creation in the midst of welfare state sabotage - Pavlina R. Tcherneva (Levy Economics Institute of Bard College, 2017)
President Trump's faux populism may deliver some immediate short-term benefits to the economy, masking the devastating long-term effects from his overall policy strategy. The latter can be termed "welfare state sabotage" and is a wholesale assault on essential public sector institutions and macroeconomic stabilization features that were built during the New Deal era and ushered in the "golden age" of the American economy. Starting in the late '70s, many of these institutions were significantly eroded by Republicans and Democrats alike, paving the way for the rise of Trump but paling in comparison with what is to come.
Keywords: H; J21; J38; L8; N12; N60; Z18; 330; Manufacturing; Service Sector; Infrastructure; Full Employment; Inequality; Social Wages; Welfare State; Trickle-down Economics